On the definition of singular bilinear forms and singular linear operators - Karwowski, W.; Koshmanenko, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We analyze various definitions of the concepts of a singular operator and a singular bilinear form and propose the most suitable ones. We also study the simplest properties of these objects.